Effect of Golden Sea Cucumber Extract (Stichopus hermanii) on Hepatic Tissue Catalase Levels in White Rats (Rattus norvegicus) Induced With High Dose Aspirin - Putri, Dyah Ayu Kusuma Ningrum Daniel (Eduvest - Journal of Universal Studies, 2025)
Aspirin, a nonsteroidal anti-inflammatory drug (NSAID), is widely used for its analgesic, antipyretic, and anti-inflammatory effects but may cause adverse effects, including hepatotoxicity. Lipid peroxidation can disrupt red blood cell function, countered by antioxidant enzymes like catalase (CAT), which is highly concentrated in the liver. This study examines the effect of golden sea cucumber (Stichopus hermanii) extract on hepatic CAT levels in aspirin-induced rats. A laboratory experiment used 24 male Wistar rats (2-3 months old, 150-200 g), divided into four groups: K1 (control, standard feed), K2 (aspirin 250 mg/kgBW), K3 (sea cucumber extract 97.2 mg/200gBW + aspirin 250 mg/kgBW), and K4 (sea cucumber extract 194.4 mg/200gBW + aspirin 250 mg/kgBW). Hepatic CAT levels were measured, yielding averages of K1 = 534.86 U/mg, K2 = 525.76 U/mg, K3 = 621.33 U/mg, and K4 = 565.24 U/mg. Normality and homogeneity tests confirmed data distribution assumptions. One-way ANOVA analysis showed no significant difference (p = 0.362, p > 0.05) between groups, indicating that golden sea cucumber extract did not significantly affect hepatic CAT levels in aspirin-induced rats. In conclusion, while Stichopus hermanii extract slightly increased CAT levels in some groups, the effect was not statistically significant. Further research is needed to explore alternative mechanisms or dosages that may enhance the hepatoprotective role of sea cucumber extract against aspirin-induced toxicity.